The project-based learning (STEM model) in fundamental physics learning - Mohamed Isa, Siti Suzilliana Putri (Global Academic Excellence (M) Sdn Bhd, 2024)
The education involves STEM combines four fields: S for Science, T for Technology, E for Engineering, and M for Mathematics. STEM education is under the Malaysian Education Development Plan (PPPM) 2013-2025, to enhance the high interest and motivation to study these four fields. Subsequently, the academic achievement of the STEM subjects can be improved. Therefore, this study aims to study the usage of the STEM model in the learning process of fundamental physics subject, characterized by higher-order thinking skills. The sample in this study was students from the Centre of Foundation Studies in Science of Universiti Putra Malaysia. Two groups are formed: the group that will produce the model (developer groups) and the group that will use the model in the learning process (user groups). The user groups are given a Pre-Achievement Test (Pre-AT) to determine their initial skills on the related topic. At the same time, the developer groups develop the STEM model, which acts as a learning tool for the usage groups. Then, after being exposed to the STEM model for 2 months, the user groups are requested to answer a Post-Achievement Test (Post-AT). The performance of Pre-AT and Post-AT are compared since these tests use a similar level of Bloom's taxonomy. Moreover, both groups need to answer the same surveys regarding the model's formation and evaluate the model's satisfaction in the learning process. Based on the analysis results, it was found that using the STEM model enhances the understanding of physics concepts, and subsequently increase the critical thinking and problem-solving skills among students. In addition, the STEM model development enhances the skills of project-based learning (PBL) among students.